The Practice of Character Strengths: Unifying Definitions, Principles, and Exploration of What’s Soaring, Emerging, and Ripe With Potential in Science and in Practice - Niemiec, Ryan M.; Pearce, Ruth (Frontiers in Psychology, 2021)
What does it mean to be "strengths-based" or to be a “strengths-based practitioner”? These are diffuse areas that are generic and ill-defined. Part of the confusion arises from the customary default of practitioners and leaders across many cultures to label anything positive or complimentary as “strengths-based,” whether that be an approach, a theoretical orientation, an intervention, or a company. Additional muddle is created by many researchers and practitioners not making distinctions between very different categories of “strength” in human beings – strengths of character, of talent/ability, of interest/passion, of skill/competency, to name a few. To add clarity and unification across professions, we offer seven characteristics and a comprehensive definition for a character strengths-based practitioner. We center on the type of strength referred to as character strengths and explore six guiding principles for understanding character strengths (e.g., character is plural; character is being and doing) and their practical corollaries. Reflecting this foundation and based on character strengths research, our longstanding work with strengths, discussions with practitioners across the globe, and a practitioner survey asking about strength practices (N=113), we point out several character strengths practices or approaches we describe as soaring (e.g., explore and encourage signature strengths; practice strengths-spotting), emerging (e.g., the integration of mindfulness and character strengths), or ripe with potential (e.g., phasic strengths; the tempering effect; the towing effect). We use the same framework for describing general research domains. Some areas of research in character strengths are soaring with more than 25 studies (e.g., workplace/organizations), some are emerging with a handful of studies (e.g., health/medicine), and others are ripe with potential that have none or few studies yet opportunity looms large for integrating character science (e.g., peace/conflict studies). Using this framework, we seek to advance the exchange and collaboration between researcher and practitioner, as well as to advance the science and practice of character strengths.